Hotel e Centro comercial - Maciel, Aline (My University, 2019)
After a market survey was carried out with the main hotels in the city, there was a need for a hotel that would cover families of all models, from traditional families with 3.4 children, as a couple + pet families. Therefore, a hotel was proposed that contemplated lodging, nature, leisure, commerce, events, ... As it is inserted in an Institutional area, it was planned in such a way that the local community could also enjoy the space without being a guest of the hotel or being a client from the shopping center. A free transitional shaft was created from the front of the ground with the back of it.(sic)
Após ser feita uma pesquisa de mercado com os principais hoteis da cidade, verificou-se a necessidade de um hotel que abrangesse famílias de todos os modelos, desde famílias tradicionais com 3,4 filhos, como famílias de casal + pet. Portanto, foi proposto um hotel que contemplasse hospedagem, natureza, lazer, comércio, eventos,... Como esta inserido numa área Institucional, foi planejado de tal maneira que a comunidade local também pudesse usufruir do espaço sem ser hóspede do hotel ou ser cliente do centro comercial. Foi criado um eixo livre de transição da parte frontal do terreno com a parte de trás dele.(sic)
Keywords: Projeto arquitetônico; Hotéis; Centros comerciais